2018
DOI: 10.1093/trstmh/try119
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi diversity in naturally infected nonhuman primates in Louisiana assessed by deep sequencing of the mini-exon gene

Abstract: Background: Trypanosoma cruzi is a zoonotic pathogen of increasing relevance in the USA, with a growing number of autochthonous cases identified in recent years. The identification of parasite genotypes is key to understanding transmission cycles and their dynamics and consequently human infection. Natural T. cruzi infection is present in captive nonhuman primate colonies in the southern USA.Methods: We investigated T. cruzi genetic diversity through a metabarcoding and next-generation sequencing approach of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
7
27
0
Order By: Relevance
“…This may be due to a combination of dogs’ immune system (DLA) and parasite strains, both of which may be highly variable. So far, most efforts at parasite genotyping in dogs have lead to the detection of TcI and TcIV in the southern USA [10], but a much greater diversity of strains covering TcI, TcII, TcIV, TcV and TcVI has been identified in Louisiana in other mammalian hosts such as rodents [38] and non-human primates [39] when using a more sensitive genotyping method based on next-generation sequencing (NGS) [40]. Infections with such a wide diversity of parasite strains in dogs may in part lead to variable immune responses as we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a combination of dogs’ immune system (DLA) and parasite strains, both of which may be highly variable. So far, most efforts at parasite genotyping in dogs have lead to the detection of TcI and TcIV in the southern USA [10], but a much greater diversity of strains covering TcI, TcII, TcIV, TcV and TcVI has been identified in Louisiana in other mammalian hosts such as rodents [38] and non-human primates [39] when using a more sensitive genotyping method based on next-generation sequencing (NGS) [40]. Infections with such a wide diversity of parasite strains in dogs may in part lead to variable immune responses as we observed.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is minimized when using conventional PCR, as generally the most common gene sequence is amplified in a reaction. However, recently, a number of deep sequencing studies reported results based on sequencing millions of copies of the SL-IR locus that seem to indicate the occurrence of almost all DTUs in infected rodents and primates in the United States (183,184). Parallel deep sequencing of appropriate biologically-cloned controls to exclude low abundance haplotypes, has thus far yielded equivocal evidence; further investigations are essential to define the applicability of this technique to characterize natural multiclonal infections (185,186).…”
Section: Issues Underlying T Cruzi Genotyping Data Collectionmentioning
confidence: 99%
“…By means of a barcoding and next-generation sequencing approach, two cases of coinfections of TcI with TcVI and TcIV were described in non-human primates from Louisiana in the southern USA (Herrera et al, 2019). The same methodological approach was used to test human T. cruzi infection, showing that Chagasic patients in Yucatan (Mexico) displayed infections by diverse T. cruzi DTUs.…”
Section: Mixed Infectionsmentioning
confidence: 99%